Efficacy and safety of 0.6% sodium alginate solution in endoscopic submucosal dissection for esophageal and gastric neoplastic lesion: A randomized controlled study. Issue 4 (18th March 2019) - Uemura, Naomi; Oda, Ichiro; Saito, Yutaka; Ono, Hiroyuki; Fujisaki, Junko; Matsuhashi, Nobuyuki; Ohata, Ken; Yahagi, Naohisa; Yada, Tomoyuki; Satoh, Masahiro; Tajiri, Hisao; Inomata, Masafumi; et al.
Abstract : Objectives: Sodium alginate (SA) solution has characteristic viscoelasticity. We aimed to determine efficacy and safety of 0.6% SA for submucosal injection during endoscopic submucosal dissection (ESD) in patients with localized neoplastic lesion in the esophageal and gastric mucosa. Methods: We conducted a randomized controlled study at six major hospitals in Japan including 130 patients with endoscopically localized neoplastic lesion in the esophageal and gastric mucosa and eligible for ESD. Patients were randomly assigned to SA or 0.4% sodium hyaluronate (SH) group (control); ESD was performed using a submucosal injection of SA/SH. As a primary outcome measure, non‐inferiority of SA against SH was investigated using en bloc complete resection in ESD and formation and maintenance of mucosal elevation upon injection as an efficacy index. Adverse events during the study were evaluated as safety outcome measures. This study was registered with Pharmaceuticals and Medical Devices Agency (clinical trial no. 28‐277/2016‐18; clinical trial identification no. KP2013‐009_C001). Results: Efficacy rate of submucosal injection during ESD was 91.7% (55/60) and 88.7% (55/62) in the SA and SH groups, respectively, demonstrating non‐inferiority of SA against SH. Adverse events for which a causal relationship with submucosal injection solution could not be eliminated were noted in 8.2% (5/61) and 4.7% (3/64) in the SA and SH groups, respectively, but symptoms disappeared without treatment/after drug administration in both groups. Conclusions: In Japan, 0.4% SH is the only commercially approved formulation for submucosal injection during ESD. The study results may expand submucosal injection solution options in clinical practice.